Phantom creation and analysis: Improving X-Ray Microtomography scanning of soft sediment cores containing volcanic ash - Richard Johnston (2016)
Poster presented at XRM 2016 (the 13th International Conference on X-Ray Microscopy) held at the Oxford Institute of Mathematics, Oxford University, run by Diamond Light Source.The poster outlines a preliminary work regarding the creation and analysis of sedimentary phantoms to inform future X-ray CT work.This work relates to a larger project investigating the effect of sedimentary reworking on the position of the tephra isochrons.A conference proceedings related to this poster is forthcoming.